Epidemiology of Liver Cancer in Africa: Current and Future Trends - Okeke, Edith; Davwar, Pantong Mark; Roberts, Lewis; Sartorius, Kurt; Spearman, Wendy; Malu, Abraham; Duguru, Mary (Seminars in Liver Disease, 2020)
Hepatocellular carcinoma (HCC) is a disease of global public health significance with mortality on the rise, despite the preventable nature of its risk factors especially in Africa. It is now the sixth most common cancer worldwide, fifth in males, and ninth in females. HCC incidence and mortality are predicted to increase in African countries constrained by limited resources to combat endemic levels of viral infection and synergistic environmental risk factors. The changing nature of HCC etiology is particularly illustrated here with the traditional risk factors like viral hepatitis coexisting alongside high human immunodeficiency virus (HIV) prevalence and rapidly increasing urbanization that have promoted a sharp increase in additional risk factors like coinfection, type 2 diabetes mellitus, and obesity. Although there are some differences in etiology between North Africa and sub-Saharan Africa, risk factors like chronic viral hepatitis B and C, aflatoxin exposure, and iron overload predominate. Aggressive hepatitis B genotypes, combined with hepatitis B virus/hepatitis C virus/HIV coinfections and aflatoxin exposure, promote a more aggressive molecular phenotype. In parallel to a better understanding of the molecular etiology of HCC, policy and planning initiatives to address the burden of HCC must be anchored within the reality of the limited resources available. Establishment and coordination of cancer registries across Africa is needed to improve the quality of data necessary to galvanize action. Preventive measures including hepatitis B vaccination programs, measures to prevent maternal-to-child and child-to-child transmission, delivery of universally accessible antiretroviral and antiviral treatments, and reduction of dietary aflatoxin exposure can contribute markedly to reduce HCC incidence. Finally, the development of biomarkers and new therapeutic interventions will need a better understanding of the unique genetic and epigenetic characteristics of HCC on the continent. We present a narrative review of HCC in Africa, discussing present and future trends.
Keywords: hepatocellular carcinoma; epidemiology; Africa; HBV/HCV/HIV/ aflatoxin coinfections; iron overload